Design of ALB Tester for Heavy Vehicle Brake Systems - Hayrettin Düzcükoğlu; Bekir Aksu (International Journal of Automotive Science and Technology, 2020)
The brake system is used to keep the speed of the moving vehicle con-stant, slow down, stop it and fix it while parked. Heavy vehicles have an air braking system. (71/320/AT) It should be produced in accordance with the regulations of motor vehicle classes and brake systems. Periodic tests should be carried out in authorized institutions. In the brake systems of vehicles in Trucks, Trailers, Trailers, Semi Trailers, Buses, load adjusting valves called ALB are used, which increase or decrease the rear brake forces of the vehicle according to the load of the vehicle. ALB can be used mechanically or pneumatically in heavy vehicles. In this study, a test device was designed us-ing the microcontroller card, pressure sensor and LCD screen in order to ena-ble the operator, who performed the pneumatic ALB test, to perform the test alone without help and to increase the reliability of the test. As a result of the study, the operator was able to perform the Pneumatic ALB test alone, in-crease the reliability, and save time and labor.